A Proposal for Implementing Entrepreneurship Courses of Specialization as an Alternative to the current Graduation Process for Obtaining the Bachelor’s Degree in Modern Languages: Specialization in French and English, Fifth-Year Students of the Public Relationship Track, School of Arts and Sciences, University of El Salvador, Semester II-2019. - Cruz Carranza, Ana Lisseth; Aguilar Hernández, Margarita; Polanco Menjívar, America Leonor (2024)
This research work is aimed at raising awareness and inform about the need to implement a specialization framework addressed to students of the Bachelor of Arts in Modern Languages: Specialization in French and English of the Foreign Language Department of the School of Arts and Sciences of the University of El Salvador, specifically those who choose the Public Relations track. In addition, the research team presents a curricular proposal that contains an appropriate academic load to the specialization. Taking into consideration the current economic situation of El Salvador and the challenges that globalization brings, Entrepreneurship has been considered as an option with great benefits and opportunities that foster spaces of grow as an alternative of life for future professionals. The research team studied the current Public Relations track graduates’ situation and the problems they are facing in the labor market due to the need for an academic restructuring of the track of Public Relations, which has not been modified since its creation in 2002. It would be advantageous for the students to have the option of being able to choose between the carrying out of a specialization that could generate more learning through experience, adequate preparation, and specialization in an area that allows graduates to find a means of economic growth for their families or the elaboration of the research work.